The determinants of the concentration of superstar firms: Cluster analysis and its relationship with economic development and artificial intelligence - José Luis Gracia Bustelo; Albert Miró Pérez; Harold Meruvia Torrez (Economies, 2025)
This study analysed the determining factors of the concentration of 'superstar firms' in specific economies, with a focus on the interaction between technological innovation, economic development, and market structures. Using global data from Statista on superstar firms for the year 2022, statistical methods such as correlation analysis, an ANOVA, and cluster analysis were applied to identify patterns and relationships between variables like the GDP, market capitalization, and the development of artificial intelligence (AI). The analysis in this paper revealed significant positive correlations between the number of superstar firms and key economic indicators such as the GDP and market capitalization, suggesting that these firms drive economic growth and technological advancement. The cluster analysis identified groupings of countries based on their technological capabilities and economic performance, highlighting that a great number of these firms are concentrated in advanced economies. This work emphasizes the importance of technological infrastructure, innovation policies, and regulatory frameworks in promoting competitive environments for superstar firms. Additionally, it addresses the socioeconomic implications, including challenges related to wealth concentration, inequality, and the transformation of the labour market. Public policies are recommended to foster inclusive innovation, STEM education, and international governance to balance global competitiveness with equitable economic growth.
Keywords: 330; superstar firms; technological innovation; economic development; artificial intelligence; regulatory policies